2009
DOI: 10.4236/jmmce.2009.810071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Leaching of Low Rank Coal and its Characterization using SEM/EDAX and FTIR

Abstract: Demineralization of coal carried out using EDTA for different time and HF of varying concentration. The residual coal from each treatment was characterized together with virgin coal using Scanning Electron Microscopy and energy dispersive X-ray analysis (EDAX). Micrograph and EDAX analysis of Virgin coal reveal the features lithophiles like aluminium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…The bright luminosity (Fig. 3C, G, K and D, H, L) is observed in the carbonized nodules, possibly due to the presence of Al, K, or Na elements in the green nodules [28]. Dark luminosity is also observed, which may be due to the presence of chalcopyrite in the green nodules [28].…”
Section: Sem Analysis Of Carbonized Nodulesmentioning
confidence: 84%
See 1 more Smart Citation
“…The bright luminosity (Fig. 3C, G, K and D, H, L) is observed in the carbonized nodules, possibly due to the presence of Al, K, or Na elements in the green nodules [28]. Dark luminosity is also observed, which may be due to the presence of chalcopyrite in the green nodules [28].…”
Section: Sem Analysis Of Carbonized Nodulesmentioning
confidence: 84%
“…However, the smooth surfaces are also observed in the micrographs of CN-2 and CN-3. The formation of holes, islands, hills, and valleys are due to the thermal shock incurred during the carbonization process [28].…”
Section: Sem Analysis Of Carbonized Nodulesmentioning
confidence: 99%
“…The FTIR spectra for the anthracites were divided into four absorption bands according to reference, i. e., hydroxyl absorption band (3600∼3000 cm −1 ), aliphatic structure absorption band (3000∼2800 cm −1 ), oxygen‐containing functional group absorption band (1800∼1000 cm −1 ) and aromatic structure absorption band (900∼700 cm −1 ), which are used for semi‐quantitative analysis of functional groups in anthracite to determine the influence of the anthracite structure on the preparation of graphene after demineralization (Figure ) . Infrared structural parameters are obtained according to the calculation method in references, including curve fitting parameters for the different absorption band area ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR analysis reveals that the leaching could not remove the mineral content completely [14]. From the EDS analysis it is confirmed that the calcites content is nil but the Al and silicates content was more compared to citric acid leaching av got dissolved at the selected pH (pH 4) and have redeposited on the surface instead of their extraction.…”
Section: Characterization Of the Demineralized Coalmentioning
confidence: 66%